Unravelling genotypic and environmental influences on strawberry (Fragaria × ananassa Duch.) fruit quality and composition across different European latitudes: Implications for climate change adaptation. - Pacheco-Ruiz, Patricia; Senger, Elisa; Pott, Delphine M.; Ziegler, Freya MR.; Masny, Agnieska; Sønsteby, Anita; Krüger, Erika; Chartier, Philippe; Mott, Daniela; Petit, Aurélie; Savini, Gianluca; Usadel, Björn; et al. (My University, 2024)
Cultivated strawberry holds a significant status as a berry crop in Europe, both economically and nutritionally. Its quality, determined by the optimal combination of organoleptic and bioactive compounds accumulated in the fresh fruit during ripening, serves as the primary appeal to consumers and renders it a valuable raw material for the industry. These attributes have resulted in global production exceeding 12.9 million tonnes (Mt) in 2020 (FAO, 2021). However, recent studies in consumer behaviour have highlighted an emerging dissatisfaction with the lack of flavour in strawberries. Although there have been advancements in understanding fruit quality, phenotyping this trait remains a challenging task due to the relatively little known about the influence of genotype-by-environment interactions (GxE). Here, we report the characterisation of GxE on the composition of four strawberry cultivars ('Clery' (IT), 'Frida' (NO), 'Gariguette' (FR), and 'Sonata' (NL)), renowned for their genetic diversity and adaptability to different geographical environments, across five European locations (Norway, Poland, Germany, Italy, and France). The integration of metabolomic, transcriptomic, and bioinformatic analyses revealed greater impact of location on quality-related metabolites in northern regions, whereas the influence of cultivar was greater in the south. We could also determine a cultivar-specific regulation of certain biosynthetic pathways involved in quality, such as terpenes, enabling us to dissect the plasticity of the genotypes and their potential as breeding material. Our findings underscore the importance of understanding the impact of GxE on quality profiles, particularly considering climate change challenges. Therefore, further multi-environment trials are needed to facilitate the recovery and enhancement of flavour and nutritional traits in future breeding programs involving strawberry fruit.
Keywords: Fresas - Genética; Plantas cultivadas - Factores climáticos; Multi-environment trial; Metabolomics; Transcriptomics; Strawberry fruit